Comprehensive Review of Universal Healthcare Issues and Innovations - Alqahtani, Fatima Essa Saad; Alqahtni, Norah Salem; Shahrani, Sultanah Faraj Abdullah Al; Zabr, Abdul Rahman Mohsen Yahya; Zabr, Meshari Mohsen Yahya; Alzulaiq, Mahdi Salem Habban; Alshamrani, Ghuzayyil Munahi Saad; Alqhtani, Fatimah salem Ayed; Alqhtani, Fouzeah Issa; Alhurais, Hamaid Saud (Journal of Ecohumanism, 2024)
The international healthcare environment of today is undergoing significant changes, with the introduction of UHC as a concept to address the gaps in fair, quality, and cost-efficient healthcare access. This literature review examines the nature of challenges that continue to arise in universal healthcare systems and the new solutions being implemented to address them. This review focuses on the impact of UHC over time across various nations, ranging from developed to developing countries, the purpose of which is to identify the challenges and practical, economic, and social considerations that may hinder the implementation of UHC as well as the strategies of innovation driving the advancement of UHC. The study identifies several trends, such as technological solutions in healthcare, changes in payment systems, reforms, and movements toward integrated health information technology. These approaches hold great potential for enhancing healthcare delivery's efficiency, scope, and viability worldwide.